PROGRAM PEMBIASAAN HARIAN DALAM MEMBANGUN BUDAYA DISIPLIN SISWA DI SMP MUHAMMADIYAH 7 KOTA MEDAN - Tiara Lubis; Abdul Fattah Nasution (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the daily habituation program implemented by Muhammadiyah 7 Middle School, Medan City. This study is based on a qualitative research approach with a descriptive nature, which allows researchers to understand the activity in depth according to field conditions. Data collection was carried out through interviews, direct observation, and documentation. The subjects of this study involved the principal, vice principal for student affairs, teachers and students. The findings of this study are classified into 3, (1) The daily habituation program policy is implemented as an effort to build a culture of student discipline, (2) The form of the daily habituation program consists of arriving on time, , 3S culture, reading prayers and short letters, memorizing vocabulary in 3 languages, opungsam culture, and congregational prayer. (3) supporting factors such as school and parental support, as well as program commitment and consistency while inhibiting factors come from students and the environment outside the school. These findings indicate that consistently implementing a daily habituation program can help foster a culture of discipline in students at school. However, there are still obstacles to implementing this habituation program, one of which is obstacles originating from the students themselves.